PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI DAN TRANSPARANSI LAPORAN KEUANGAN TERHADAP KUALITAS PELAYANAN PASIEN BPJS DI RUMAH SAKIT ISLAM FATIMAH BANYUWANGI - Hafifatul Nurhayati; Roni Yanto (Accounting Journal of Ibrahimy (AJI), 2026)
An Accounting Information Systems (AIS) was a series of systems used by various institutions to process and store data, ranging from administration to the finance department, so that it produced information for those in need. Financial report transparency was the openness regarding financial information of an institution to the parties in need. Meanwhile, ervice quality consisted of all behaviors and features of services and products that supported the services towards the satisfaction of customer needs, both directly and indirectly. According to the result of interviews and observations at RSI Fatimah Banyuwangi, the implementation of AIS and financial report transparency were not maximally implemented. This study was conducted with the aim to identifyi the influence of accounting information system and financial report transparency on the service quality of BPJS patient at RSI Fatimah Banyuwangi. This research used a quantitative method. The main data used was primary data obtained through the distribution of questionnaires to respondents. The sampling technique in this study used the total sampling technique, which included all members of the population as samples, totaling 50 respondents. Data were analyzed using multiple linear regression analysis. The results of this study stated that the implementation of AIS and financial report transparency simultaneously influenced the service quality of BPJS patients at RSI Fatimah Banyuwangi.